cho xy+yz+zx=1 tinh tong x*can((1+y^2)(1+z^2)/(1+x^2))+y*can((1+x^2)(1+z^2)/(1+y^2))+z*can((1+y^2)(1+x^2)/(1+z^2))
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^2+y^2+z^2=xy+yz+zx\)
\(\Leftrightarrow\)\(x^2+y^2+z^2-xy-yz-zx=0\)
\(\Leftrightarrow\)\(2x^2+2y^2+2z^2-2xy-2yz-2zx=0\)
\(\Leftrightarrow\)\(\left(x-y\right)^2+\left(y-z\right)^2+\left(z-x\right)^2=0\)
\(\Leftrightarrow\)\(\hept{\begin{cases}x-y=0\\y-z=0\\z-x=0\end{cases}}\)\(\Leftrightarrow\)\(x=y=z\)
\(A=\left(1+\frac{x}{y}\right)\left(1+\frac{y}{z}\right)\left(1+\frac{z}{x}\right)=\left(1+1\right)\left(1+1\right)\left(1+1\right)=8\)
Cho x, y, z > 0 và x+y+z=1.
CMR : \(\dfrac{1-x^2}{x+yz}+\dfrac{1-y^2}{y+zx}+\dfrac{1-z^2}{z+xy}\ge6\)
Ta có : \(\frac{1}{x}+\frac{1}{y}+\frac{1}{z}=0\)
\(\Rightarrow\left(\frac{1}{x}+\frac{1}{y}\right)^3=-\frac{1}{z^3}\)
\(\Rightarrow\frac{1}{x^3}+\frac{1}{y^3}+3\cdot\frac{1}{xy}\left(\frac{1}{x}+\frac{1}{y}\right)+\frac{1}{z^3}=0\)
\(\Rightarrow\frac{1}{x^3}+\frac{1}{y^3}+\frac{1}{z^3}=-3\cdot\frac{1}{xy}\left(\frac{1}{x}+\frac{1}{y}\right)=-3\cdot\frac{1}{xy}\cdot\left(-\frac{1}{z}\right)=\frac{3}{xyz}\)
Khi đó có : \(P=\frac{yz}{x^2}+\frac{zx}{y^2}+\frac{xy}{z^2}=xyz.\left(\frac{1}{x^3}+\frac{1}{y^3}+\frac{1}{z^3}\right)=xyz\cdot\frac{3}{xyz}=3\)
GT \(\Leftrightarrow xy+yz+zx=0\). Khi đó: \(\left(xy\right)^3+\left(yz\right)^3+\left(zx\right)^3=3.xy.yz.zx=3x^2y^2z^2\).
Do đó: \(P=\frac{\left(xy\right)^3+\left(yz\right)^3+\left(zx\right)^3}{x^2y^2z^2}=3\)
\(\dfrac{x-y}{z^2+1}=\dfrac{x-y}{z^2+xy+yz+zx}=\dfrac{x-y}{z\left(z+y\right)+x\left(z+y\right)}=\dfrac{x-y}{\left(x+z\right)\left(z+y\right)}\)
Tương tự: \(\dfrac{y-z}{x^2+1}=\dfrac{y-z}{\left(x+y\right)\left(x+z\right)}\);\(\dfrac{z-x}{y^2+1}=\dfrac{z-x}{\left(x+y\right)\left(y+z\right)}\)
Cộng vế với vế \(\Rightarrow VT=\dfrac{x-y}{\left(x+z\right)\left(y+z\right)}+\dfrac{y-z}{\left(x+y\right)\left(x+z\right)}+\dfrac{z-x}{\left(x+y\right)\left(y+z\right)}\)
\(=\dfrac{\left(x-y\right)\left(x+y\right)+\left(y-z\right)\left(y+z\right)+\left(z-x\right)\left(z+x\right)}{\left(x+y\right)\left(y+z\right)\left(z+x\right)}\)
\(=\dfrac{x^2-y^2+y^2-z^2+z^2-x^2}{\left(x+y\right)\left(y+z\right)\left(z+x\right)}=0\)(đpcm)